External load diffrences between elite youth and professional football players: ready for take-off? - Houtmeyers, K. C.; Jaspers, A.; Brink, M. S.; Vanrenterghem, J.; Varley, M. C.; Helsen, W. F. (Science and Medicine in Football, 2020)
This study examines differences in weekly load between the first (FT) and the under 19 team (U19) within a professional football setting. Data were collected in 11 FT and 9 U19 players (2016-2017 season). FT data was divided into weeks with (FT-M1) or without (FT-M0) a mid-week match. Indicators were total distance (TD) and TD at 12-15, 15-20, 20-25 and >25 km*h-1 and were analysed as external load (m), intensity (m*min-1) and load monotony (a.u.). TD-based load was higher for U19 compared to FT-M0 (very likely moderate) and FT-M1 (likely large). Differences at higher velocities were substantially less (trivial to possibly small), with TD >25 km*h-1 being lower than FT-M0 (very likely moderate) and FT-M1 (likely small). All intensity indicators were lower for U19 (likely small to almost certainly large). Load monotony was higher compared to FT-M1 (possibly small to almost certainly very large). Compared to FT-M0, monotony was higher for TD (possibly very large) and TD >25 km*h-1 (possibly moderate) but lower for TD 12-15 (possibly small) and 15-20 km*h-1 (likely moderate). So, despite higher weekly external loads at low velocity for elite youth players, external intensity and load variation increases when these players may transition to professional football.